READINESS FOR INTERPROFESSIONAL EDUCATION AND COLLABORATION AMONG NURSING STUDENTS - Sarah Kartika Wulandari; Putu Inge Ruth Suantika; Putu Rusanti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Effective healthcare delivery requires complex collaboration among all professionals involved, including nurses. Patient care in clinical settings relies heavily on teamwork between health workers across disciplines. One strategy to strengthen such collaboration is Interprofessional Education and Collaboration (IPE-C), which prepares students to work effectively in interprofessional teams. Assessing students’ readiness for IPE-C is essential for integrating it into health education programs. This study aimed to assess nursing students’ readiness to engage in IPE-C during their educational experience.Methods: This mixed-method study involved 659 nursing students from levels I to IV of the undergraduate nursing program and the professional nursing program at ITEKES Bali. Data were collected between June and August 2023 using a modified version of the Readiness for Interprofessional Learning Scale (RIPLS). Quantitative data were analyzed using the Kruskal-Wallis test to compare readiness levels across groups. Qualitative data were analyzed thematically.Results: Quantitative findings showed that students in Levels I and II had the highest overall competency scores (mean score = 4). There were statistically significant differences among the five student groups regarding competencies related to negative professional identity, positive professional identity, and roles and responsibilities (p < 0.001). However, no significant differences were found in the teamwork and collaboration domain (p > 0.05). Qualitative analysis identified three major themes: (1) uncertainty about the role and responsibilities of the nursing profession, (2) fear of making mistakes, and (3) eagerness to experience IPE-C in future clinical practice.Conclusion: Nursing students demonstrate readiness to engage in IPE-C during their academic training, though variations exist in specific competencies. To support this readiness, nursing curricula should incorporate interprofessional education as a dedicated subject, offering both theoretical and practical exposure at the academic level.